How Much Time are Physicians and Nurses Spending Together at the Patient Bedside?. Issue 8 (1st August 2019) - Sang, Adam X; Tisdale, Rebecca L; Nielsen, Derek; Loica‐Mersa, Silvia; Miller, Travis; Chong, Ian; Shieh, Lisa
Abstract : BACKGROUND: Bedside rounding involving both nurses and physicians has numerous benefits for patients and staff. However, precise quantitative data on the current extent of physician–nurse (MD–RN) overlap at the patient bedside are lacking. OBJECTIVE: This study aimed to examine the frequency of nurse and physician overlap at the patient beside and what factors affect this frequency. DESIGN: This is a prospective, observational study of time‐motion data generated from wearable radio frequency identification (RFID)‐based locator technology. SETTING: Single‐institution academic hospital. MEASUREMENTS: The length of physician rounds, frequency of rounds that include nurses simultaneously at the bedside, and length of MD–RN overlap were measured and analyzed by ward, day of week, and distance between patient room and nursing station. RESULTS: A total of 739 MD rounding events were captured over 90 consecutive days. Of these events, 267 took place in single‐bed patient rooms. The frequency of MD–RN overlap was 30.0%, and there was no statistical difference between the three wards studied. Overall, the average length of all MD rounds was 7.31 ± 0.58 minutes, but rounding involving a bedside nurse lasted longer than rounds with MDs alone (9.56 vs 5.68 minutes, P < .05). There was no difference in either the length of rounds or the frequency of MD–RN overlap between weekdays and weekends. Finally, patient rooms located farther away from the nursing station had a lower likelihood of MD–RN overlap (Pearson's r = –0.67, P < .05). CONCLUSION: RFID‐based technology provides precise, automated, and high‐throughput time‐motion data to capture nurse and physician activity. At our institution, 30.0% of rounds involve a bedside nurse, highlighting a potential barrier to bedside interdisciplinary rounding. Abstract :